Vanuatu : 2011 Article IV Consultation; Staff Report; Debt Sustainability Analysis; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
Vanuatu showed signs of a moderate rebound in economic activity owing to its good macroeconomic fundamentals and a supportive international community. Executive Directors encouraged the authorities to tighten monetary policy in response to rising inflation pressures. They emphasized the need to strengthen fiscal buffers to safeguard the hard-earned fiscal soundness. Directors underscored the need to safeguard external buffers by maintaining an adequate level of foreign exchange reserves. They encouraged further efforts to strengthen the regulatory and supervisory framework that covers the whole financial system.